FACILITIES IN FOOD MARKET INFRASTRUCTURE - Bahodirjon Nosirov; Akbarali Abdurashidov (International Journal of Business, Law and Political Science, 2024)
Market infrastructure is crucial in shaping the regional food market. The market infra-structure is composed of two main pillars: the organizational base, which includes wholesale and retail trade networks, exchanges, and dealers, and the material base, which includes warehouses, transport, and marketing services. Details about develop-ing the food market in Andijan province are given in this article. Regional market management is a concept that provides regional authorities with a long-term plan and options for its implementation. Utilizing it, one can establish methods for developing market relations; determine the socio-economic and environmental parameters for re-gional market development; compare them to real opportunities; implement a system of economic and legal management of regional markets